Studi Proses Pembentukan Pendidikan Budi Pekerti Melalui Pembelajaran Agama Islam di SMA Negeri 3 Jombang - Asep Kurniawan; Suwandi (Menara Tebuireng, 2017)
Establishing a virtuous man is one of the aspect of national education objectives as stated in Law No. 20 of 2003, in Chapter II, Article 3 which explains that "national education is functioning to develop the ability and form the character and civilization of a dignified nation in order to educate the life of the nation, aims for the development of noble character. Character education has been applied through religious education. The purpose of this study are: (a) to know how the relevance of Islamic learning to the mind in SMAN 3 Jombang, and (b) to know how the process of cultivating the values ​​of character in SMAN 3 Jombang?. This research is a qualitative research model, with case study approach (case study). The location of this study took at one of the schools located in Jombang namely SMAN 3 Jombang. This research get some findings or results, namely: (a) Relevance of religious learning in SMAN 3 Jombang against manners is that the study of religion is the basic foundation to be a guide in life and it is reflected in the values ​​of manners that have been implanted among them; manners, tolerance, discipline, awareness of obligatory worship and sunnah, courtesy of teachers and caring, keeping the cleanliness and beauty of the school; (b) The process of cultivating the values ​​of character in SMAN 3 Jombang is done through religious learning process that includes reading, identifying, discussing, interpreting, and practicing activities. Besides the approach of religious learning is done by using faith approach, morals, psychological, sociological, philosophical (reasoning) and religious learning materials include several aspects, among the aspects of faith, Islamic laws, morals are neatly arranged in the lesson plan and learning syllabus. While the method of religious learning used is a lecture model, question and answer, discussion, and inquiry. The evaluation model on the learning of religion is in several ways, namely evaluation on the process, evaluation on the results, and also evaluation on the practice